AN ASSOCIATION OF CYTOKINE LEVELS WITH DISEASE ACTIVITY, AUTOANTIBODY LEVELS, AND JOINT DESTRUCTIVE CHANGES IN EARLY RHEUMATOID ARTHRITIS - A. S. Avdeeva; A. A. Novikov; E. N. Aleksandrova; D. E. Karateev; A. V. Smirnov; E. L. Luchikhina; E. L. Nasonov (Научно-практическая ревматология, 2015)
Objective: to assess the association of cytokine profile measures with disease activity, autoantibody levels, and joint destructive changes in patients with early rheumatoid arthritis (RA).Subjects and methods. Forty-five patients, including 35 women, with early RA were examined. Their median age was 53.5 [46; 59.5] years; the duration of the disease – 7.0 [4.0; 11.5] months; DAS28 – 5.8 [4.9; 6.4]; 91 and 96% of the patents were positive for rheumatoid factor (RF) and anticyclic citrullinated peptide antibodies, respectively. Serum cytokine concentrations were estimated using the xMAP multiplex technology. The modified Sharp method was employed to quantify radiographic changes.Results and discussion. A group of 30 patients with high disease activity (DAS28 >5.1) had higher levels of interleukin (IL)-6 (62.3 [36.1; 127.5] pg/ml) and IP-10 (6367.8 [3682.7; 10691.3] pg/ml than 15 patients with moderate/low disease activity (DAS28 ≤5.1) (35.8 [13.4; 64.2] and 3222.6 [1881.0; 5671.9] pg/ml, respectively, p < 0.05). The patients highly positive for IgM RF had higher levels (pg/ml) of proinflammatory cytokines, such as IL-1β, IL-2, IL-6, IL-12, IL-15, interferon-γ, and tumor necrosis factor-α; the chemokine monocyte chemotactic protein-1 and the growth factors IL-7 and vascular endothelial growth factor (4.8 [2.8; 19.3], 23.0 [7.1; 55.8], 64.2 [41.6; 170.5], 52.2 [30.9; 126.9], 2.4 [0.2; 11.2], 210.8 [119.9; 584.2], 90.7 [42.7; 307/9], 57.5 [26.1; 93.8], 54.9 [37.1; 123.7], and 143.3 [70.6; 249.6] pg/ml) than those who were negative/lowly positive for IgM RF (2.3 [1.9; 3.1], 4.9 [2.9; 16.8], 24.9 [20.4; 45.4], 25.6 [19.9; 57.1], 0.2 [0.01; 1.65], 94.4 [86.3; 138.9], 37.3 [23.6; 47.7], 20.9 [12.3; 33.9], 32.6 [28.1; 37.8], 74.2 [53.5; 147.6], respectively (p < 0.05)).Conclusion. There are significant differences in cytokine profile measures in patients with early RA in relation to disease activity and serum autoantibody levels.